2014
DOI: 10.1179/1743284713y.0000000388
|View full text |Cite
|
Sign up to set email alerts
|

Differential scanning calorimetry study of constrained groove pressed low carbon steel: Recovery, recrystallisation and ferrite to austenite phase transformation

Abstract: Low carbon steel sheets are subjected to severe plastic deformation (SPD) via constrained groove pressing (CGP) up to five passes. As a result of this process, strain magnitude up to 5·8 is imposed to the sheets, which leads to grain size of 225 nm. These nanostructured steel sheets, due to their high dislocation density and ultrafine microstructure, are very sensitive to heating. In the present study, recovery, recrystallisation and ferrite to austenite phase transformation phenomena for the SPD steel are inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Furthermore, the heavily deformed structure both facilitates nucleation processes and promotes a higher driving force for recrystallization, which results in the shift of this process toward lower temperatures. This observation is in agreement with the analogous shift of recrystallization temperature reported for a 0.05 wt% C (non‐martensitic) steel after SPD and a 0.2 wt% C martensite after rolling . The large variation of plastic strain from the center to the edge of a HPT disk is a possible explanation for the large broadening of the DSC peak.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the heavily deformed structure both facilitates nucleation processes and promotes a higher driving force for recrystallization, which results in the shift of this process toward lower temperatures. This observation is in agreement with the analogous shift of recrystallization temperature reported for a 0.05 wt% C (non‐martensitic) steel after SPD and a 0.2 wt% C martensite after rolling . The large variation of plastic strain from the center to the edge of a HPT disk is a possible explanation for the large broadening of the DSC peak.…”
Section: Discussionsupporting
confidence: 90%
“…In higher number of passes, the decrease in UTS and elongation is observed in all treated samples and the rate of strength improvement is also decreased for the as‐deformed samples. These may be attributed to dislocation annihilation in deformation stage, appearance of microcracks, microstructural evolution during the annealing stage, and the effect of strain amount on the shift of transformation regions in Fe − C phase diagram …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Khodabakhshi et al showed that for the samples deformed more than 1 pass of CGP, dislocation density gradually decreased, so it is expected that in our experiment, less routes are available for carbon to diffuse and redistribute in the earlier stages of annealing when the samples experienced higher strains. Additionally, as the gradual transition of low‐angle grain boundaries to high‐angle grain boundaries may take place through deformation process, grain growth can follow the recrystallization and phase transformation processes during the annealing stage in samples processed by 2 and 3 CGP passes, while the recrystallization temperature itself is shown to remain almost constant at higher amounts of deformation . Consequently, it is expected that larger ferrite grain size in combination with higher concentration of carbides along the grain boundaries is obtained through annealing after higher strains.…”
Section: Resultsmentioning
confidence: 99%
“…This ultra-grain refinement brings about exceptional mechanical properties based on the Hall-Petch theory [7]. So far, special processing techniques of severe plastic deformation have been developed and used in order to fabricate UFG metals and alloys, including equal channel angular extrusion (ECAE) [8][9][10], high pressure torsion (HPT) [11][12][13], accumulative roll bonding (ARB) [14][15][16], twist extrusion (TE) [17][18][19], simple shear extrusion [20], severe forward extrusion (SFE) [21], and constrained groove pressing (CGP) [22][23][24]. ECAE is one of the most well developed SPD processing techniques in which the material is deformed through a die with two channels intersecting at a certain angle, which is described completely in previous reports [25,26].…”
Section: Introductionmentioning
confidence: 99%